Evaluation of Croatian-speaking children's speech with cochlear implants and comparison with hearing-aid users - Mildner, Vesna (Array, 2003)
Twenty-one prelingualy deaf children with cochlear implants, aged between 5 and 13 years and all monolingual Croatian speakers were studied. The aim was to evaluate the speech of implanted children, depending on the age at implantation, and the duration of pre- and postoperative rehabilitation. The speech samples were collected by having the children describe a series of cartoons depicting a birthday scene. Speech therapists and university students evaluated the recordings. The listeners had to reconstruct the story based on the heard renditions and to evaluate the speech for voice quality and overall intelligibility on a 1-5 scale. The samples were also analysed in terms of utterance complexity and the prevalence of different word types. Comparison with the matched group of non-implanted deaf children, all hearing-aid users, reveals differences between the two groups of children with respect to both the linguistic and phonetic parameters.